Hubungan antara Konsep Diri dengan Penyesuaian Sosial Remaja Lembaga Kesejahteraan Sosial Anak (LKSA) di Makassar - Arnitasari Arnitasari; Eva Meizara Puspita Dewi; Kurniati Zainuddin (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
Social adjustment is one of the most difficult and important developmental tasks of adolescents to help adolescents deal with their environment and society. Social adjustment is influenced by various factors, one of which is self-concept. Positive self-concept can help teenagers to making good social adjustments. This study aims to determine the relationship between self-concept and social adjustment in adolescents who live in orphanage in Makassar. The research subjects were 91 teenagers from orphanage in Makassar, which were selected using accidental sampling technique. The measuring instrument used is the self-concept scale and the social adjustment scale. The data analysis technique in this research uses the spearman rho correlation test. The results of data analysis showed a correlation coefficient of 0.391 with a significance value of 0.000 (p<0.05). The value of the correlation coefficient (r=0.391) shows that there is a positive relationship between self-concept and social adjustment in adolescents from orphanage in Makassar. A positive value on the correlation coefficient shows that the higher the self-concept, the higher the social adjustment, or vice versa. Implications: This study implies that improving self-concept in adolescents is needed to improve their social adjustment in social environment.